2012
DOI: 10.1177/193758671200500403
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Comparison of Open-Bay and Single-Family-Room Neonatal Intensive Care Units at Sanford Children's Hospital

Abstract: These data overwhelmingly support the SFR NICU in preference to the traditional OPBY facility. They substantiate that the SFR NICU should be the new standard for NICU care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 36 publications
2
61
0
2
Order By: Relevance
“…3 Further, current recommendations for NICU design include construction of private space to reduce environmental stimulation to the infant and support family involvement. 8 Positive staff and caregiver perceptions, 9-11 decreased noise levels and nosocomial infections, 12, 13 and lower rates of readmission in the months after discharge 14 were reported following NICU renovation to private rooms. A randomized clinical trial conducted in Sweden reported reductions in length of stay among infants assigned to single family rooms, consisting of private space for the family and infant, and in which parents were required to be present from admission to discharge.…”
mentioning
confidence: 99%
“…3 Further, current recommendations for NICU design include construction of private space to reduce environmental stimulation to the infant and support family involvement. 8 Positive staff and caregiver perceptions, 9-11 decreased noise levels and nosocomial infections, 12, 13 and lower rates of readmission in the months after discharge 14 were reported following NICU renovation to private rooms. A randomized clinical trial conducted in Sweden reported reductions in length of stay among infants assigned to single family rooms, consisting of private space for the family and infant, and in which parents were required to be present from admission to discharge.…”
mentioning
confidence: 99%
“…[8][9][10][11] Some of these inconsistencies could be due to methodologic issues. of NICU may be inadequate to explain potential differences, be they positive or negative, and that it is critical to study why such differences are observed.…”
Section: Figurementioning
confidence: 99%
“…These include a shorter interval until full enteric feedings; fewer apneic events; reductions in mortality, nosocomial sepsis, 2 length of stay, [3][4][5] rehospitalization, 4 cost, 6 and noise; increases in breastfeeding, 2 family-centered care, parent visitation, privacy and satisfaction 3,[6][7][8] ; more positive staff perceptions of the environment 2 and job quality 9 and less nurse anxiety. 10 However, negative effects have also been reported including increased number of staff, 10 poorer quality of staff interaction, 9,11 and increased maternal stress. 8 Alterations in brain structure and function have also been reported among infants in private NICU rooms in a NICU with poor family involvement.…”
mentioning
confidence: 99%
“…The noise level is higher in multibed than single-bed rooms (8,10,18), and noise increases subjective stress, annoyance, sympathetic nervous system activation (19), and sleep disruption (8). It has been proved that sleep disruption and the consequent deprivation are associated with an increase in delirium prevalence (20) and confirming that association, the use of ear plugs during the night decreases the delirium prevalence in ICU patients (21).…”
Section: Hypotheses For the Difference In Delirium Prevalencementioning
confidence: 87%